Large Intronic Deletion of the Fragile Site Gene PRKN Dramatically Lowers Its Fragility Without Impacting Gene Expression - Munk, Sebastian H. N.; Voutsinos, Vasileios; Oestergaard, Vibe H. (Frontiers in Genetics, 2021)
Common chromosomal fragile sites (CFSs) are genomic regions prone to form breaks and gaps on metaphase chromosomes during conditions of replication stress. Moreover, CFSs are hotspots for deletions and amplifications in cancer genomes. Fragility at CFSs is caused by transcription of extremely large genes, which contributes to replication problems. These extremely large genes do not encode large proteins, but the extreme sizes of the genes originate from vast introns. Intriguingly, the intron sizes of extremely large genes are conserved between mammals and birds. Here, we have used reverse genetics to address the function and significance of the largest intron in the extremely large gene PRKN, which is highly fragile in our model system. Specifically, we have introduced an 80-kilobase deletion in intron 7 of PRKN. We find that gene expression of PRKN is largely unaffected by this intronic deletion. Strikingly, the intronic deletion, which leads to a 12% reduction of the overall size of the PRKN gene body, results in an almost two-fold reduction of the PRKN fragility. Our results stress that while the large intron clearly contributes to the fragility of PRKN, it does not play an important role for PRKN expression. Taken together, our findings further add to the mystery concerning conservation of the seemingly non-functional but troublesome large introns in PRKN.